Intracavitary/Interstitial Applicator Plus Distal Parametrial Free Needle Interstitial Brachytherapy in Locally Advanced Cervical Cancer: A Dosimetric Study - Qu, Hong-Da; Han, Dong-Mei; Zhang, Ning; Mao, Zhuang; Cheng, Guang-Hui (Frontiers in Oncology, 2021)
Purpose To explore the dosimetric advantage of combining intracavitary/interstitial applicator with distal parametrial free needle interstitial brachytherapy (IC/IS+ISBT DP) based on MRI for locally advanced cervical cancer. Methods and Materials 77 IC/IS+ISBT DP treatment plans were developed for 34 patients with locally advanced cervical cancer from June 2016 to January 2020 in this study. We removed the free needles and devised a new IC/ISBT treatment plan based on the same principle. We then compared the dosimetric differences of D90, D98, V100, V150, V200 for HR-CTV (high-risk clinical target volume), D90 for IR-CTV (Intermediate risk-CTV) and D2cc for OARs (organs at risk) between the two groups of treatment plans for the same patient, and the paired T test was performed in parallel. Further, the dosage differences between the two group plans under different parametrial extension widths (the maximum distance of HR-CTV from the vertical direction of the uterine tandem at coronal position) were compared. The survival rate was calculated using the Kaplan-Meier method. Prognostic factors for overall survival (OS) and progression-free survival (PFS) were determined by Cox regression method. RTOG/EORTC criteria were used to grade toxicities. Results A total of 297 free needles were used, with a weight ratio of 15.8% ± 0.11, and a mean insertion depth of 6.52cm ± 2.8cm. D90, D98, V100 for HR-CTV, and D90 for IR-CTV for IC/IS+ISBT DP were significantly higher than IC/ISBT for which free needles were removed (p<0.05). And the V200 for HR-CTV and D2cc for bladder, rectum and sigmoid were decreased (p<0.05). When the parametrial extension widths were greater than 3cm, the HR-CTV D90 and the D2CC for rectum, bladder and sigmoid colon for IC/IS-ISBT DP were advantageous compared to IC/ISBT (p<0.05). The 2-yr OS, PFS and local control rate (LC) were 82.3, 66.8, and 93.1%, respectively. Parametrial extension widths was the only statistically prognostic factors for PFS (p = 0.002) on univariate analysis. No grade 3 or 4 Treatment-related toxicities were observed. Conclusion Our institutional experiences showed that IC/IS+ISBT DP is an effective treatment for cervical cancer patients with distal parametrial extension. IC/IS-ISBT DP had dosage advantage and clinical feasibility in locally advanced cervical cancer with distal parametrial extension when the parametrial extension widths were greater than 3cm.